Human papillomavirus-specific antibody status among unvaccinated subjects in the region of Vojvodina, Serbia - Kovačević, Gordana; Božić Nedeljković, Biljana; Patić, Aleksandra; Radovanov, Jelena; Hrnjaković-Cvjetković, Ivana (Central European journal of public health, 2023)
OBJECTIVES: The aim of the study was to evaluate the immune status of young people from the Vojvodina province, Serbia, through the detection of IgG antibodies specific for the L1 protein of HPV types 6, 11, 16, and 18 contained in quadrivalent vaccine. METHODS: The study enrolled 514 healthy persons of both genders, aged between 18 and 30 years. All potential participants were informed about the project's aims by trained interviewers before venous blood collection. Also, participants completed a specially designed anonymous questionnaire to identify socio-demographic characteristics and individual behaviours associated with HPV seroprevalence. VPL HPV L1-specific IgG antibodies were measured using a semi-quantitative HPV IgG ELISA kit (Dia.Pro, Italy). RESULTS: A total of 472 (91.8%) young subjects had no detectable antibodies against high- and low-risk HPV types covered by the quadrivalent vaccine. A slightly higher number of seropositive individuals were detected in the age group of 26-30 years compared to younger than 25. Multivariate analysis showed that the number of lifetime sexual partners was the most powerful predictor of HPV seropositivity (OR = 3.483, 95% CI: 1.294-9.379). CONCLUSIONS: Obtained data point out low levels of naturally induced HPV-specific serum antibodies among the target population in the Vojvodina province. The present work highlights the significance and potential benefits of HPV vaccination. Routine HPV vaccination should be the public health priority in our country and should be included in the national immunization programme as soon as possible.
Keywords: dospělí; Vaccines, Combined; Human Papillomavirus Viruses; Female; Papillomavirus Infections; lidské papilomaviry; Yugoslavia; imunoglobulin G; Adult; Srbsko; mladý dospělý; ženské pohlaví; Papillomavirus Vaccines; Adolescent; kombinované vakcíny; lidé; Serbia; Jugoslávie; protilátky virové; Immunoglobulin G; human papillomavirus; séroepidemiologické studie; ELISA; Male; Seroepidemiologic Studies; Young Adult; infekce papilomavirem; mužské pohlaví; vakcíny proti papilomavirům; Antibodies, Viral; L1 antigen; anti-HPV IgG antibodies; mladiství; Humans